The effects of carbohydrate intake and muscle glycogen content on self-paced intermittent-sprint exercise despite no knowledge of carbohydrate manipulation - Skein, M.; Duffield, R.; Kelly, B. T.; Marino, F. E. (European Journal of Applied Physiology, 2012)
The aim of this study was to determine the effects of carbohydrate (CHO) ingestion and muscle glycogen content, without the influence of knowledge of CHO consumption, on intermittent-sprint performance. Ten males completed two conditions on two consecutive days. Day 1 involved 2 × 40 min of leg cycling separated by 15 min of arm cycling, followed by an overnight diet consuming either a high [HCHO; 7 g/kg body weight (bw)] or low (LCHO; 2 g/kg bw) CHO diet. Participants were blinded to the knowledge CHO was being examined or manipulated. Day 2 included a 60-min intermittent-sprint exercise (ISE) protocol that included 15-m maximal sprints every minute and self-paced efforts of varying intensities. Pre and post-ISE muscle biopsies were obtained on Day 2. Pre- and post-exercise maximal voluntary torque (MVT), voluntary activation (VA) and twitch contractile properties were assessed during 15 maximal isometric contractions. Blood glucose and lactate, heart rate (HR) and rating of perceived exertion (RPE) were also recorded. Pre-ISE muscle glycogen was greater in HCHO compared with LCHO (597 ± 115 vs. 318 ± 72 mmol kg dry weight; P = 0.001). Total distance and hard running distance were 4.9 and 8.1% greater in HCHO, respectively (P = 0.02-0.04). Peak MVT, VA, HR and RPE were not different between conditions (P > 0.05). Blood glucose was higher pre-ISE for LCHO but lower post-ISE compared with HCHO (P < 0.05). These results indicate HCHO improved self-paced exercise intensities during the ISE protocol despite no knowledge of dietary manipulation. Due to the blinded study design, exercise intensities seem manipulated due to peripheral perturbations associated with CHO content rather than a conscious manipulation of exercise intensities.